2022
DOI: 10.1002/smtd.202200209
|View full text |Cite
|
Sign up to set email alerts
|

High‐Voltage, Highly Reversible Sodium Batteries Enabled by Fluorine‐Rich Electrode/Electrolyte Interphases

Abstract: High energy density and long‐term cycling stability are crucial factors for the commercialization of sodium batteries in large scale. In this regard, cathode materials that can operate at high voltage have attracted great interest owing to their high energy density. However, traditional electrolytes cannot be used in high‐voltage sodium batteries due to their limited oxidative stability. Therefore, there is a great challenge to develop appropriate electrolytes for high‐voltage cathode materials. Herein, a dilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…This is better than most previous reported high-voltage SMBs (Table S1). [37][38][39][40][41][42][43] Moreover, there is only slight voltage polarization and degradation at ultra-high charging voltage (Figure 2c, S10), indicating superior oxidative toleration and superior compatibility with high-voltage NVPF cathode for DA electrolyte.…”
Section: Methodsmentioning
confidence: 99%
“…This is better than most previous reported high-voltage SMBs (Table S1). [37][38][39][40][41][42][43] Moreover, there is only slight voltage polarization and degradation at ultra-high charging voltage (Figure 2c, S10), indicating superior oxidative toleration and superior compatibility with high-voltage NVPF cathode for DA electrolyte.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, ionic liquid (IL) electrolytes containing various anions and cations have also drawn considerable attention in Na-based batteries because of Fig. 14 (a) The XPS spectra results for the Na metal anode in NCPP8Na cells after 100 cycles at a current density of 0.5 mA cm À2 with a capacity of 0.5 mA h cm À2 in different electrolytes and schematic representation of the CEI and SEI formation, 220 (b) seawater battery configuration and proposed mechanisms of NaBH 4 /glyme electrolytes, 178 (c) electrochemical performance of symmetrical Na|Na cell at current density of 1 mA cm À2 and capacity of 1 mA h cm À2 , and schematic illustration of the SEI formed from the wet P 111i4 FSI electrolyte under different current density and capacity. 226 their non-flammable and non-volatile nature, low freezing point and chemical stability.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%
“…The reduction of the NaDFOB salt results in the formation of borate-and fluoride-rich SEI, which prevents the decomposition of carbonate solvents 159,175. Guo et al revealed that the Frich SEI is beneficial in inhibiting the continuous decomposition of electrolytes and Na dendrites growth 220. As shown in Fig.14a, the C-F and NaF peaks with high intensity were observed from XPS spectra results for Na8Na 4 Co 3 (PO 4 ) 2 P 2 O 7 (NCPP) cells after 100 cycles in 1 m NaPF 6 -FEC/DMC (2 : 8) electrolyte.…”
mentioning
confidence: 99%
“…As an explanation, carbonate solvents, such as propylene carbonate (PC) (Figure S1), have a low highest occupied molecular orbital (HOMO) energy level and thus show good antioxidant abilities . With regard to fluorinated solvents, such as ethoxy­(pentafluoro)­cyclotriphosphazene (PFPN) (Figure S1), a large amount of electronegative fluorine atoms inside can improve their antioxidant abilities and the subsequent formation of fluorinated interphase can profoundly improve anodic electrochemical stability. , By taking full advantage of these solvents, they could be added as a co-solvent in a small proportion into cyclic ether-based electrolytes to improve the antioxidant ability of the whole electrolyte. In this way, the electrolyte not only keeps the low-temperature feature resulting from ether solvent but also obtains improved antioxidant abilities as the reason of the co-solvents.…”
Section: Introductionmentioning
confidence: 99%